Therapeutic use of pulsed electromagnetic field therapy reduces prostate volume and lower urinary tract symptoms in benign prostatic hyperplasia - Tenuta, Marta (Andrology, 2020)
BACKGROUND: Benign prostatic hyperplasia (BPH) etiology remains poorly understood, but chronic low‐grade inflammation plays a role. Pulsed electromagnetic field therapy (PEMF) (1‐50 Hz) is effective in reducing tissue inflammation. OBJECTIVES: We designed a pilot study to evaluate the effects of PEMF on prostate volume (PV) in BPH. MATERIALS AND METHODS: This is a prospective interventional trial on 27 naive patients with BPH and lower urinary tract symptoms (LUTS). At baseline (V(0)), all patients had blood tests, transrectal ultrasound, and questionnaires (IPSS, IIEF‐15) and received a perineal PEMF device (Magcell(®)Microcirc, Physiomed Elektromedizin). PEMF was delivered on perineal area 5 minutes twice daily for 28 days, then (V(1)) all baseline evaluations were repeated. Afterward, nine patients continued therapy for 3 more months (PT group) and 15 discontinued (FU group). A 4‐month evaluation (V(2)) was performed in both groups. RESULTS: A reduction was observed both at V(1) and at V(2) in PV: PV(V0) 44.5 mL (38.0;61.6) vs PV(V1) 42.1 mL (33.7;61.5, P = .039) vs PV(V2) 41.7mL (32.7;62.8, P = .045). IPSS was reduced both at V(1) and at V(2): IPSS(V0) 11 (5.7;23.2) vs IPSS(V1) 10 (6;16, P = .045) vs IPSS(V2) 9 (6;14, P = .015). Baseline IPSS was related to IPSS reduction both at V(1) (r(s) = 0.313;P = .003) and at V(2) (r(s) = 0.664;P < .001). PV reduction in patients without metabolic syndrome (ΔPV(V1nMetS) −4.7 mL, 95%CI −7.3;‐2.0) was greater than in affected patients (ΔPV(V1MetS) 1.7 mL, 95%CI −2.69;6.1)(P = .017, Relative Risk(MetS) = 6). No changes were found in gonadal hormones or sexual function. DISCUSSION: PEMF was able to reduce PV after 28 days of therapy. Symptoms improved in a short time, with high compliance and no effects on hormonal and sexual function or any side effects. Patients with moderate‐severe LUTS and without MetS seem to benefit more from this treatment. CONCLUSION: PEMF reduces PV and improves LUTS in a relative short time, in BPH patients. These benefits seem greater in those patients with moderate‐severe LUTS but without MetS.